Organophosphate Poisoning Management in a Primary Healthcare Facility in Nigeria: A Case Report - Erhiori, Akponah; Kohworho, Umukoro Emuesiri; Blessing, Elijah Oghenekparobor; Vincent-Junior, Igben Onoriode (Asian Journal of Advanced Research and Reports, 2025)
Background: Organophosphate poisoning causes a range of symptoms affecting multiple organ systems. Delayed presentation and diagnosis may be catastrophic and ultimately fatal. The population most at risk are young adults, and in our environment where health seeking behaviour does not favour early presentation in the hospitals, management is challenging especially in primary health facilities with limited capacity to test and manage. Objective: The objective of this case report is to describe the presentation, investigation and management of a case of organophosphate poisoning in a primary health centre (PHC). Case Presentation: We report our experience in managing a 21 year old female patient who presented following ingestion of an organophosphate containing poison about 7 hours post incident. She was drowsy at presentation and history was given by her sister. She was stabilized, managed with atropine and fluids. Her general condition improved significantly over the first 24 hours and she was discharged on the 4th day post admission. A referral to a psychiatrist was made on discharge. We discuss relevant considerations of management of such poisonings, the clinical features, investigations and outcomes. We also discuss the limitations with management of these cases in our setting. Conclusion: Incidence of organophosphate poisoning is increasing and mortality rates are relatively high due to late presentation and delays in management. Furthermore, limitations in primary care centres with distant referral centres puts a demand on the primary care physician to institute all life saving and initial management before referral. The index case was managed as a case of organophosphate poisoning secondary to a suicide attempt with a favourable outcome and subsequent referral to a psychiatrist. A high index of suspicion is needed in an environment with a young population.